Okinawa and the U.S. military identity making in the age of globalization - Inoue, Masamichi S. 1962- (Columbia University Press, 2007)
In 1995, an Okinawan schoolgirl was raped by several US servicemen. Reaction to the crime culminated in a rally attended by some 85,000 people. Using this event as a point of reference, this book explores how Okinawans began to regard themselves as a confident citizenry embracing ideals of democracy, human rights, and women's equality